Legal Protection for A Bona Fide Buyer of A Certificate of Ownership Acquired Through an Unregistered Sale and Purchase Agreement - Anggraini, Fransisca Mayra; Marniati, Felicitas Sri; Putri Syakura, Furcony (CV. Publikasi Indonesia, 2025)
The sale and purchase of land represent a legally binding relationship as stipulated in Article 1233 of the Indonesian Civil Code, formed through mutual agreement between the seller and the buyer. Despite the existence of clear legal provisions, informal or underhanded land sale practices remain prevalent, particularly in rural regions. These unregistered transactions often lead to complications in the transfer of land ownership, especially when the original landowner is no longer traceable. This study aims to explore the legal mechanisms for transferring land ownership certificates to buyers acting in good faith and to assess the legal protection available in the absence of registered land sale agreements. The research employs a normative juridical method, grounded in legal theories from Satjipto Rahardjo on legal protection and Subekti on agreements. The study analyzes secondary data through statutory, case, and conceptual approaches, supported by legal document identification and inventory techniques. The findings indicate that buyers in good faith must pursue court rulings to validate ownership rights when faced with informal land transactions. Such rulings serve as a legal basis to register the land transfer at the local Land Office. This approach upholds the principle of legal certainty and provides protective mechanisms for individuals affected by non-notarial land transactions, encouraging future land dealings to adhere to formal registration processes to protect ownership rights.